Self-efficacy and Career Adaptability in Early Career employees - Stephany G. Holderman; Sutarto Wijono (Faculty of Psychology, Universitas Semarang, 2024)
Abstract. Every company strives to increase efficiency and effectiveness to adapt to competitive developments. One of the efforts made is to prepare employees to compete at work. Career adaptability is necessary for employees to support effective performance, especially for early career employees. Therefore, early career employees need good self-efficacy to support career adaptability. This research aims to determine the relationship between self-efficacy and career adaptability in early-career employees at PT. XYZ. The method used is quantitative with a simple correlational design. Data collection used non-probability sampling with a saturated sampling technique, carried out using a Google form distributed to all PT. XYZ. The research scale consists of the General Self-Efficacy Scale (α =0.932) and the Career Adapt-Abilities Scale (α= 0.969). The Spearman Rho correlation test obtained a coefficient value of 0.841 with p(Sig.) = 0.000 (p<0.01) shows that self-efficacy positively relates to career adaptability in early-career employees. Research on self-efficacy and career adaptability in early career employees is expected to provide important information that can be used to improve employee development practices, organizational policies, and future academic literature.Keywords: Self-efficacy; Career Adaptability; Early Career